Impact of Switching From Clopidogrel To Ticagrelor on Adverse Cardiovascular Events in Patients With ST-Segment Elevation Myocardial Infarction - Tavlueva, Evgeniya; Alekseenko, Alexey; Gruzdeva, Olga; Uchasova, Evgenya; Barbarash, Olga (Cardiology and Cardiovascular Medicine, 2018)
Aim: to assess the impact of switching from clopidogrel to ticagrelor on clinical endpoints in the in-hospital period and 1 year post-discharge in patients with ST-segment elevation myocardial infarction (STEMI). Methods: Eighty patients with STEMI were included in the study. All patients received a loading dose of aspirin (250 mg) and clopidogrel (600 mg) in the ambulance. Groups 1 and 2 patients received a maintenance dosage of 75 mg clopidogrel daily and 90 mg ticagrelor twice daily, respectively. Clinical endpoints were assessed on day 8 in the in-hospital period and 1 year post-discharge. The platelet aggregation and plasma levels of interleukin-6 (IL-6) and C-reactive protein (CRP) were measured before and on day 7 after switching from clopidogrel to ticagrelor. Results: A trend toward fewer clinical endpoints was found in the ticagrelor group compared with the clopidogrel group. There was no significant increase in the rate of bleeding in the in-hospital period and within 1 year after STEMI in the ticagrelor group compared with the clopidogrel group. On day 8 of the in-hospital period, platelet aggregation was significantly higher in the clopidogrel group than that in the ticagrelor group (p = 0.00). The CRP and IL-6 levels on day 8 of the in-hospital period were significantly higher in the clopidogrel group than those in the ticagrelor group (p = 0.04 vs. p = 0.01, respectively). Conclusion: Switching from clopidogrel to ticagrelor on day 1 after myocardial infarction was associated with lower rate of endpoints during the 1-year follow-up.